Mitochondrial Effects on the Physiological Characteristics of Lentinula edodes - Minseek Kim; Seong-Hyeok Yang; Hui-Gang Han; Eunbi Kim; Sinil Kim; Youn-Lee Oh; Hyeon-Su Ro (Mycobiology, 2022)
AbstractIn the mating of filamentous basidiomycetes, dikaryotic mycelia are generated through the reciprocal movement of nuclei to a monokaryotic cytoplasm where a nucleus of compatible mating type resides, resulting in the establishment of two different dikaryotic strains having the same nuclei but different mitochondria. To better understand the role of mitochondria in mushrooms, we created four sets of dikaryotic strains of Lentinula edodes, including B2 × E13 (B2 side) and B2 × E13 (E13 side), B5 × E13 (B5 side) and B5 × E13 (E13 side), E8 × H3 (E8 side) and E8 × H3 (H3 side), and K3 × H3 (K3 side) and K3 × H3 (H3 side). The karyotypes and mitochondrial types of the dikaryotic strains were successfully identified by the A mating type markers and the mitochondrial variable length tandem repeat markers, respectively. Comparative analyses of the dikaryotic strains on the mycelial growth, substrate browning, fruiting characteristics, and mitochondrial gene expression revealed that certain mitochondria are more effective in the mycelial growth and the production of fruiting body, possibly through the activated energy metabolism. Our findings indicate that mitochondria affect the physiology of dikaryotic strains having the same nuclear information and therefore a selection strategy aimed at mitochondrial function is needed in the development of new mushroom strain.